An interesting phenomenon in immigrant spouses and elderly suicides in Taiwan. (January 2018) - Lai, Ying-Chieh; Chen, I-Hui; Miao, Nae-Fang; Hsiao, Yu-Ling; Li, Hsien-Chang
Highlights: The elderly face conflicts caused by different cultures from immigrate spouses (i.e., daughter/son in law of immigrants), influencing their well-being. However, it is unclear whether immigrant spouses and elderly suicides display the same trends. This is the first longitudinal study to explore the relationships between immigrant spouses and suicides in older adults. As for gender differences, only female immigrant spouses had a significant positive relationship with elder suicides. Abstract: Background: Immigration is a global issue. Taiwan has a high proportion of immigrant spouses who take care of the aging parents-in-law at home mainly based on filial piety. Difficulties in communication in many aspects of daily life occur between the elderly and immigrant spouses, and result in the elderly becoming vulnerable and thus, influencing their psychological well-being. Although past studies demonstrated that due to cultural differences, employed foreign care providers negatively influenced elder care quality (e.g., care receipts' health or mortality rates), no studies have explored whether immigrant spouses, as family caregivers, have any influence on elderly suicides due to cross cultural communication differences. Objective: To address the above gap, this study was to examine the static relationship between immigrant spouses and elderly suicides. Method: National-level authority data, comprising a 10-year longitudinal nationwide sample, were used. The number of immigrant spouses was treated as a proxy of cultural differences. Twelve models of outcomes with and without city- and time-fixed effects were conducted using panel data analysis. Results: Descriptive statistics of the study variables are provided. The results revealed that overall the number of immigrant spouses had a positive correlation with suicides in older adults. Further, the gender of immigrant spouses had different impacts on elderly suicides. Conclusions: This is the first study to examine relation between immigrant spouses and the elderly suicides. The study results provide another viewpoint of understanding of the role of immigrant spouses in elder care, while promoting elder-caregiver interactions for optimal elder health outcomes.